PENGARUH KEPERCAYAAN KONSUMEN, CITRA MEREK, DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN PADA MARKETPLACE BLIBLI.COM - Jacob, Maura Aliciana Jauvanka; Sarah, Siti (Media Mahardhika, 2024)
Blibli is one of the B2C (Business to Consumer) marketplace platforms, serving as a pioneer in the Indonesian online shopping industry. It strives to fulfill the need for an enhanced user experience in online shopping activities, aiming to be the premier choice for online shopping in Indonesia. The focus of this research is to investigate how consumer trust as a variable (X1), brand image as a variable (X2), and service quality as a variable (X3) can influence customers in making purchasing decisions on the Blibli marketplace. Additionally, the study aims to identify which aspect most significantly affects purchasing decisions on the Blibli marketplace. The analytical method employed in this research involves the analysis of preprocessed data using SPSS version 26. Validity and reliability tests, classical assumption tests (including heteroskedasticity, multicollinearity, normality tests), and multiple linear regression analysis are utilized. Reliable data is gathered from a sample of 100 participants, chosen through a non-probability sampling strategy. Findings indicate that consumer trust, brand image, and service quality collectively influence purchasing decisions on the Blibli marketplace. However, brand image and service quality do not have a significant impact on purchase decisions. These findings assist users in making more informed purchase choices on the site. Furthermore, the research offers insights into characteristics that have a significant impact on purchase decisions, aiding Blibli in allocating resources effectively.